The influence of political and social globalisation on foreign direct investment inflow in developing countries: the role of financial development as a moderating factor / Marhamah Mohd Rafidi ...[et al.] - Mohd Rafidi, Marhamah; Said, Jamaliah; Erum, Naila; Abdol Ghapar, Farha (Universiti Teknologi MARA, 2021)
This study presents the effect of political and social globalisation on Foreign Direct Investment (FDI) inflow in developing countries. The eminence of decomposed globalisation element in the FDI area is argued here. New insights into empirical evidence are offered by dropping economic globalisation as one of the decomposed components. A panel data of 42 developing countries from 1984 until 2016 was used by applying the CSARDL approach. The study is also on the impact of political and social globalisation in developing countries by splitting them into two income stratification: Upper Middle-income Countries and Lower Middle-Income Countries by incorporating financial development as a moderating variable. It documents that political globalisation postulates a U-shaped relationship after addressing the Cross-Sectional Dependence (CD) problem, while social globalisation reverses the U-shaped relationship. It was found that political globalisation and social globalisation are conditional to the level of income rather than the overall developing countries' stream. Besides, the prominent role of financial development in promoting FDI inflow, especially to income level, was observed. We suggest that developing countries should increase the capacity to absorb political and social globalisation in promoting FDI.